Production of biosurfactant by Cunninghamella elegans UCP 0542 using food industry waste in 3 L flasks and evaluation of orbital agitation effect (Research, Society and Development, 2022)
In current study, the production of biosurfactant by Cunninghamella elegans UCP 0542 in food industry waste-based medium was investigated as a biotechnological strategy to reduce the bioprocess costs. Cultivation of the Mucoralean fungus was performed in 3 L Fernbach flasks containing 1.5 L of effective volume of medium composed by 2% instant noodle waste, 2% corn steep liquor and 0.5% post-frying soybean oil, with carbon/nitrogen ratio of 30:1. Fermentations were carried out during 96 h and 28ºC, at 150, 180 and 200 rpm, in order to evaluate the influence of orbital agitation in biosurfactant production. The properties of surface tension reduction, emulsification and dispersion were investigated. According to the obtained results, C. elegans produced biosurfactant in sustainable medium, reducing the surface tension from 71 to 27.5 mN/m after cultivation at 200 rpm. Biotensoactive produced in this condition formed stable emulsions with engine oil and burnt engine oil (emulsification index of 100%) and showed 48.39 cm² of oil dispersion area (ODA) with burnt engine oil. The biomolecule was isolated by different methodologies, reaching a maximum yield of 2.1 g/L with ethanol. The biosurfactant produced by C. elegans exhibited excellent potential for application in bioremediation processes considering its promising properties as a surface tension reducing agent, emulsifying and dispersing action of petroderivatives.